Revolutionizing Oncology: Iron Oxide Nanoparticles in Cancer Diagnosis and Treatment (International Journal of Scientific Research in Science and Technology, 2025)
Iron oxide nanoparticles (IONPs) have emerged as a transformative tool in oncology, offering unprecedented opportunities for early cancer diagnosis and effective treatment. These nanoparticles exhibit unique physicochemical properties, including superparamagnetism, biocompatibility, and a large surface area-to-volume ratio. These properties make them particularly suitable for applications such as high-resolution imaging, targeted drug delivery, and hyperthermia therapy. Additionally, their ability to be functionalized with various biomolecules enables precision targeting of cancerous tissues, further enhancing their efficacy. This article delves into the cutting-edge advancements in the utilization of IONPs, examines their multifunctional roles in oncology, addresses the challenges in their clinical translation, and outlines future directions for research and application in this dynamic field.